Determine of the nira water viscosity by using video based laboratory falling ball method with tracker software - Rianita Bela Islami; Lalu A. Didik; Bahtiar Bahtiar (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika)
This study aims to determine the viscosity of sap water using a falling ball method based on a video based laboratory with tracker software. This type of research is experimental research with a quantitative approach. The viscosity of sap water is measured by varying the temperature, concentration and duration of fermentation. The temperature varied, namely 16 C, 27 C and 82 C. The concentrations were varied by comparing the viscoefficient value of pure sap water, sap water added with coconut water and mineral water. And for the fermentation time of the sap water was varied for 7 days, 9 days and 11 days of fermentation. The sap water with varying temperature, concentration and fermentation time has different coefficient values for the sap water. The sap water given the highest temperature has the lowest viscosity coefficient value. And the sap water with the highest concentration has the highest viscosity coefficient value as well. And the longest fermented juice showed the lowest value of the viscosity coefficient of sap water.